Smallholder dairy production and markets: a comparison of production systems in Zambia, Kenya and Sri Lanka - Moll, H.A.J.; Staal, Steven J.; Ibrahim, Mohamed N.M. (Elsevier, 2007)
Three smallholder dairy production systems in Zambia, Sri Lanka and Kenya are analysed and compared. The focus is on the relationships between the animal production system, the farm household system, and the institutional environment. Attention is given to the valuation of marketed and non-marketed products and the intangible benefits of livestock in insurance, financing and status display. The comprehensive and comparative analysis of the production systems shows the direct relationship between type and intensity of dairy production and the presence or absence of markets for milk and other products, services and employment. The generally unobserved income components resulting from products other than milk and from the intangible benefits prove to be a substantial proportion of the total income in all three systems. The comprehensive perspective on the dairy production system results in policy suggestions that include institutional linkages.